Mapped aboveground carbon stocks to advance forest conservation and recovery in Malaysian Borneo. (January 2018) - Asner, Gregory P.; Brodrick, Philip G.; Philipson, Christopher; Vaughn, Nicolas R.; Martin, Roberta E.; Knapp, David E.; Heckler, Joseph; Evans, Luke J.; Jucker, Tommaso; Goossens, Benoit; Stark, Danica J.; Reynolds, Glen; et al.
Abstract: Forest carbon stocks in rapidly developing tropical regions are highly heterogeneous, which challenges efforts to develop spatially-explicit conservation actions. In addition to field-based biodiversity information, mapping of carbon stocks can greatly accelerate the identification, protection and recovery of forests deemed to be of high conservation value (HCV). We combined airborne Light Detection and Ranging (LiDAR) with satellite imaging and other geospatial data to map forest aboveground carbon density at 30 m (0.09 ha) resolution throughout the Malaysian state of Sabah on the island of Borneo. We used the mapping results to assess how carbon stocks vary spatially based on forest use, deforestation, regrowth, and current forest protections. We found that unlogged, intact forests contain aboveground carbon densities averaging over 200 Mg C ha −1, with peaks of 500 Mg C ha −1 . Critically, more than 40% of the highest carbon stock forests were discovered outside of areas designated for maximum protection. Previously logged forests have suppressed, but still high, carbon densities of 60–140 Mg C ha −1 . Our mapped distributions of forest carbon stock suggest that the state of Sabah could double its total aboveground carbon storage if previously logged forests are allowed to recover in the future. Our results guide ongoing efforts to identify HCV forests and to determine new areas for forest protection in Borneo.